Metabolomic changes in tear fluid following zinc biofortification in the BiZiFED nutritional study: a feasibility study - Brown, Connor N.; Shahzad, Babar; Zaman, Mukhtiar; Pan, Xiaobei; Green, Brian D.; Lowe, Nicola M.; Lengyel, Imre (Frontiers in Molecular Biosciences, 2024)
Biofortified Zinc Flour to Eliminate Deficiency in Pakistan (BiZiFED) is a nutritional research program that evaluates the impact of consuming zinc biofortified wheat flour on zinc status and associated health outcomes of vulnerable communities in northwest Pakistan. Measuring zinc status from blood samples is fraught with problems. This feasibility study evaluated whether metabolite changes in tear biofluids could be used to understand zinc status. Zinc deficiency is particularly prevalent amongst the female population in Pakistan. Therefore, a crossover trial was developed in which 25 women of reproductive age received standard, wheat flour, and another 25 received zincbiofortified wheat flour for 8 weeks. At the end of this period, the nutritional intervention was switched between the groups for another 8 weeks. Tear biofluid was collected using Schirmer strips at baseline and after 8 and 16 weeks. Metabolomic analysis was conducted using the MxP® Quant 500 kit on the tear biofluid from a subset of the study participants. Two metabolites had a significantly negative correlation with plasma zinc concentration: tiglylcarnitine and valine. Compared to baseline metabolite concentrations, acetylcarnitine, glutamine, two lysophosphatidylcholines (lysoPC a C16:0 and lysoPC a C18:1), and four sphingomyelins (SM (OH) C16:1, SM C16:0, SM C16:1, and SM C24:0) were all significantly decreased post-zinc intervention, whilst a ceramide (Cer(d18:1/18:0) was significantly increased. These results highlight the potential of using tear biofluids as an alternative source for metabolomic biomarkers, both for the assessment of the zinc status of individuals enrolled in nutritional studies and for indicating physiological changes that arise from nutritional supplementation.